2021
DOI: 10.1016/j.diabres.2021.108750
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 lockdown on glucose control of elderly people with type 2 diabetes in Italy

Abstract: Aims: to evaluate the effect of home confinement related to COVID-19 lockdown on metabolic control in subjects with T2DM in Italy. Methods: we evaluated the metabolic profile of 304 individuals with T2DM (65% males; age 69 ± 9 years; diabetes duration 16 ± 10 years) attending our Diabetes Unit early at the end of lockdown period (June 8 to July 7, 2020) and compared it with the latest one recorded before lockdown. Results: There was no significant difference in fasting plasma glucose (8.6 ± 2.1 vs 8.8 ± 2. 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 14 publications
4
40
3
1
Order By: Relevance
“…In general, we analyzed n = 1823 T2D patients. Of n = 8 T2D studies, n = 4 (50%) showed clear deteriorations in glycemic control (HbA1c and mean glucose) [ 39 42 ], n = 2 (25%) showed stability (no changes) [ 43 , 44 ] and n = 2 (n = 25%) [ 45 , 46 ] improvements. In n = 5 of n = 8 T2D studies, the patients received telemedicine care, but telemedicine was not described in detail, and in n = 3 papers no digital treatments were described.…”
Section: Resultsmentioning
confidence: 99%
“…In general, we analyzed n = 1823 T2D patients. Of n = 8 T2D studies, n = 4 (50%) showed clear deteriorations in glycemic control (HbA1c and mean glucose) [ 39 42 ], n = 2 (25%) showed stability (no changes) [ 43 , 44 ] and n = 2 (n = 25%) [ 45 , 46 ] improvements. In n = 5 of n = 8 T2D studies, the patients received telemedicine care, but telemedicine was not described in detail, and in n = 3 papers no digital treatments were described.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies have indicated that people with T2D have seen their HbA1c rise during COVID [ 27 , 28 ] but in at least one of these studies the rise has been for people with diabetes less than 50 years of age [ 27 ] but not older. Balancing these observations are studies showing that COVID-19 home confinement did not negatively impact glucose control in patients with T2D [ 29 ], although older age and insulin therapy are associated with greater risk of deterioration of glucose control, and a separate study has observed a fall in HbA1c during the COVID restrictions [ 30 ]. A study from the Netherlands found that, during the COVID-19 lockdown, people with relatively well-controlled T1D or T2D showed increased stress and weight gain but no deterioration in glucose control [ 31 ].…”
Section: Diabetes Control In Absence Of Telemonitoringmentioning
confidence: 99%
“…Increased snacking, poor dietary habits and reduced physical activity have been shown to contribute for worsening of glycaemic status [ 15 , 16 ], and is comparable with our study. Ruiz-Roso et al [ 17 ] demonstrated that patients aged 63 years or younger significantly increased their sugar intake, whereas Falcetta et al [ 18 ] showed that older patients (>80 years) were at risk of worsened glycaemic control during the COVID-19 lockdown. However, age was not an independent predictor of glycaemic control in our study.…”
Section: Discussionmentioning
confidence: 99%